Implementation of a new research tool for evaluating Mediterranean Sea Literacy (MSL) of high school students: A pilot study - CHEIMONOPOULOU, MARIA; KOULOURI, PANAYOTA; PREVIATI, MONICA; REALDON , GIULIA; Mokos, Melita; Mogias, Athanasios (Mediterranean Marine Science, 2022)
The Mediterranean Sea is recognized as a key component in the development, economy, and culture of European, North African, and Middle East countries. With respect to heterogeneity across the region in different sectors, Ocean Literacy, though still in its infancy, is nevertheless a requisite for a better understanding of the two-way interaction between the Sea and its people. In the present study, marine issues in relation to the content knowledge of 154 high school students from the Mediterranean region were investigated by using a structured questionnaire based on the recently published Mediterranean Sea Literacy guide. Data analysis involved descriptive statistics to portray frequencies and knowledge scores of the participants, and inferential statistics to assess the eﬀects of grade level on students’ knowledge. The study which focused for the first time on the unique features of the Mediterranean marine ecosystems, found the level of content knowledge of the participants to be low to moderate. It is therefore of the utmost importance for the organizations and networks working on marine issues in the Mediterranean Sea to develop synergies and coordinate research programmes to broaden engagement with human societies in the region.